Epidemiological analysis of developmental dysplasia of the hip in live births in the Unified Health System (Research, Society and Development, 2022)
The objective of this trial is to analyze the diagnosed profile of developmental dysplasia of the hip (DDQ) the number of babies born alive in Brazil from 2016 to 2020. This is a descriptive, retrospective and analytical study, about the hospitalizations resulting from DDQ, International Code of Diseases (ICD) Q650 to Q659, elaborated through secondary data obtained from the Sistema de Informações sobre Nascidos Vivos do Sistema Único de Saúde (SISNAC/SUS), made available by the Departamento de Informática do SUS (DATASUS), in newborns, during the period from 2016 to 2020, in Brazil. During the analyzed period, 1.150 diagnoses for congenital hip deformities were registered in the number of babies born alive in Brazil. Regarding the ICD of congenital hip deformities, the largest number of cases is concentrated in ICD Q650, unilateral congenital dislocation of the hip, with 410 cases (35.65%), followed by ICD Q652, specific congenital hip dislocation, responsible for 202 cases (21.29%). As reported about the ethnicity of the new borns, the highest number of cases prevailed in children of brown ethnicity, with a total of 553 cases (448.08%). In the second place was the white ethnicity accounted for 475 cases (41.30%). Conclusion: Therefore, this survey shows that the cases of developmental dysplasia of the hip per year, in newborns, present an approximate value, without great variations. This highlights the need for epidemiological delimitation, so that public policies, aimed at both treatment and prevention, can be directed.